EMPIRICAL PARKING STUDY IN UNIVERSITY OF DUHOK CAMPUS - ASWAD, NAHLA HUSSEIN (Journal of Duhok University, 2021)
University of Duhok campus in Duhok city, Kurdistan region, Iraq, suffers from a serious mobility problems and illegal on-street parked cars resulting from continuous development of campus withoutproper policy and program to control the problem. The aim of this paper is to present empirical parking study in University of Duhok (UoD) campus by assessing and examining the present supply of parking. Besides, it aims to find the maximum expected number of parking spaces that would be able to accommodate the current parked vehicles, and the expected number of parking spaces to accommodatethe future demand of spaces. Several related parking surveys were conducted in the university campus, involved: current parking supply, computing the available off street parking capacity, license plate survey and questionnaire survey for campus parkers. The UoD main campus inventory results indicated that there are 2,027 available spaces which distribute on 27 lots. Campus parkers’ behavior has been evaluated from quantitative samples (more than 600) of parkers. Data was collected laterally nine hours by observing and recording the vehicles license plate number to study vehicles parking duration. It was observed that a massive number of vehicles were parked with short parking duration and the maximum parking index was appeared from 10:30 a.m. to 11:00 a.m. With the continuous progress in campus population and land uses development for different purposes, the UoD main campus suffers from insufficient supply spaces for parkers. In addition to that, it is estimated that the parking spaces demand will remain to growth in the forthcoming years due to the campus circumstance.